2013
DOI: 10.1155/2013/849602
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Bodily Self-Awareness during Acupuncture Needle Stimulation Using the Rubber Hand Illusion

Abstract: Background. The rubber hand illusion (RHI) is an experimental paradigm that manipulates important aspects of body self-awareness. Objectives. We were interested in whether modifying bodily self-awareness by manipulation of body ownership and visual expectations using the RHI would change the subjective perception of pain as well as the autonomic response to acupuncture needle stimulation. Methods. Acupuncture needle stimulation was applied to the real hand during the RHI with (experiment 1) or without (experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…In the current study, we found no significant differences of subjective DeQi ratings between the two sessions. Even though there were two different characteristics of acupuncture sensations, such as the pain domain and DeQi domain [41] , our findings are partially supporting the previous findings that there were no differences of pain ratings during the RHI [36] , [49] . Although we did not find significant differences of subjective DeQi ratings between the two sessions, differences of brain activations to acupuncture stimulation in the posterior insula was associated with the difference of DeQi sensation between the two sessions in the current study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the current study, we found no significant differences of subjective DeQi ratings between the two sessions. Even though there were two different characteristics of acupuncture sensations, such as the pain domain and DeQi domain [41] , our findings are partially supporting the previous findings that there were no differences of pain ratings during the RHI [36] , [49] . Although we did not find significant differences of subjective DeQi ratings between the two sessions, differences of brain activations to acupuncture stimulation in the posterior insula was associated with the difference of DeQi sensation between the two sessions in the current study.…”
Section: Discussionsupporting
confidence: 89%
“…Mohan et al have failed to demonstrate that the RHI modulate pain threshold or pain evoked by individually calibrated high and low painful stimuli delivered on the real arm [49] . Our previous study also found no significant differences in self-reported pain rating to acupuncture stimulation between the asynchronous and the synchronous session [36] . In the current study, we found no significant differences of subjective DeQi ratings between the two sessions.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…We also expect that our study can improve the sense of immersion in VR based clinical applications, such as treatment for phantom limb pain [33] and pain relief during acupuncture [34]. A network of multisensory and homeostatic brain areas was reported to be responsible for maintaining a “body-matrix” [35].…”
Section: Discussionmentioning
confidence: 99%